1990
DOI: 10.1177/0734242x9000800135
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes Towards Glass Recycling in Scotland

Abstract: This paper describes a research project into public attitudes towards glass recycling in Scotland which was undertaken with the objective of identifying ways of increasing the recycling rate. Interviews were carried out of users and non-users at a number of sites in different districts in Scotland with the object of ascertaining the knowledge of glass recycling, motivation and behaviour of both groups. The results gave considerable insights into the types of people that were involved in recycling, their aspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The proportion of recyclers making special journeys to recycle (7-9% at supermarket sites) in the current survey were quite comparable with the numbers found in previous surveys, 13% (MEL, 1989), 9% (Ball and Lawson, 1990). Round trip lengths of 0Ð68-6Ð04 miles (1Ð09-9Ð66 km) were also consistent with the figures found in previous research.…”
Section: Comparison With Previous Researchsupporting
confidence: 93%
See 1 more Smart Citation
“…The proportion of recyclers making special journeys to recycle (7-9% at supermarket sites) in the current survey were quite comparable with the numbers found in previous surveys, 13% (MEL, 1989), 9% (Ball and Lawson, 1990). Round trip lengths of 0Ð68-6Ð04 miles (1Ð09-9Ð66 km) were also consistent with the figures found in previous research.…”
Section: Comparison With Previous Researchsupporting
confidence: 93%
“…Indeed, as far as we are aware, few data have ever been published on the scale of impacts that may ensue. Ball and Lawson (1990) found that most users of bring schemes in various sites around Scotland would use cars (71%) and that most stated their journey to recycle would be a combined trip to recycle and use shops (85%) with only 9% making a special journey to recycle. The distances travelled were not investigated however and no figures were given on the mode of transport used for the special journeys.…”
Section: Introductionmentioning
confidence: 98%
“…. Situational factors; variables representing an individual's situation at a given time may affect their environmental action, such as access to services, age or gender [22][23][24]. .…”
Section: Environmental Behaviourmentioning
confidence: 99%
“…However, in relation to individuals, a number of studies have highlighted the passive nature of the acquisition of knowledge for action, e.g., through seeing recycling facilities, recycling scheme leaflets, the media, shops and supermarkets, and information passed on from friends and trusted others [33,84,[122][123][124][125]. Steedman [125] focused on the acquisition of knowledge and described actively seeking out information on EAs as a "specialist concern" (p. 1) as only 19% of consumers had sought out information on at least one topic and only 8% on five or more topics.…”
Section: Determining Factorsmentioning
confidence: 99%